(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SUMMARY: 1. Introduction - 2. The Vertical and Horizontal Influences - 3. Atheism, laïcité and Church - 4. Atheism, laïcité and Islam - 5. Today’s Popular Sources of Atheism - 6. Conclusion. ABSTRACT: With this article, the Author outlines the legal issues involving the atheism in France, analysing them in the light of the principle of laïcité. France has a long history of criticism of religion. Many philosophes of the Enlightenment, for example, have provided the classical writings in this field. In this sense, they were able to aliment two major streams of thought of the magmatic French atheism: one is based on the horizontal influences arising from the effect of increasing worldwide travel with the discovery that people do not necessary share the same views and beliefs about the nature of human being; the other is centred on vertical arguments bubbling up from the past in a very form of scepticism and realism. With its multi-faceted and articulated view, the French atheism has also been promoted by a number of movements devoted to arguing the case for non-belief and for its political expression in laïcité. In this manner, the Author tries to demonstrate that, since the Great Revolution and during the long history of the French constitutional system, laïcité de combat and atheism has been influencing each other in a constantly shifting process of mutual adaptation.